Ocena efektywności polskich inwestycji zagranicznych - wyniki badań - Jaworek, Małgorzata; Szóstek, Aneta (The Appraisal of Polish Foreign Direct Investment - The Research Results, 2008)
This paper discusses the issue of the appraisal of foreign direct investment projects undertook by Polish investors. It deeply analyzes obstacles which Polish investors had to face starting the activity abroad. The article also presents the issues concerning an evaluation of incomes from the foreign investment, a discount rate or an application of measures of the projects effectiveness.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 231-242